Podori na Dobraču - Zorn, Matija (Geografski vestnik, 2002)
Due to their size Mt. Dobratsch rock-falls (Austria) have been often mentioned in Slovenian geographical and geological literature referring to rock-falls and slope processes. Modern Austrian historiography has relatively late joined the researches of the Dobratsch rock-falls consequences. We may therefore say that it is partly responsible for the fact that some incorrect notions on the 1348 Mt. Dobratsch rock-falls, so called historical, still exist in the Slovenian literature. Hereby we would like to present recent findings of Austrian historiography so as to abolish false notions about the consequences of 1348 Mt. Dobratsch rock-falls. Geomorphological characteristics of rock-falls are also discussed. More stages of rock-falls are defined on Mt. Dobratsch and the 1348 "Villach earthquake" characteristics and consequences are described as well.
Keywords: Dobrač; Beljak; Ziljska dolina; geomorfologija; geomorphology; podori; potresi; zgodovinski pregledi